2D and 3D amplitude‐preserving elastic reverse time migration based on the vector‐decomposed P‐ and S‐wave records. (16th September 2020) - Zhang, Wei; Gao, Jinghuai; Gao, Zhaoqi; Shi, Ying
ABSTRACT: The elastic reverse time migration approach based on the vector‐wavefield decomposition generally uses the scalar product imaging condition to image the multicomponent seismic data. However, the resulting images contain the crosstalk artefacts and the polarity reversal problems, which are caused by the nonphysical wave modes and the angle‐dependent reduction of image amplitudes, respectively. To overcome these two problems, we develop an amplitude‐preserving elastic reverse time migration approach based on the vector‐decomposed P‐ and S‐wave seismic records. This approach includes two key points. The first is that we employ the vector‐decomposed P‐ and S‐wave multicomponent records to independently reconstruct the PP and PS reflection images to mitigate the crosstalk artefacts. The second is that we propose two schemes in addressing the issue of polarity reversal problem in the conventional PP image. One solution is to adopt the angle‐dependent equation. Another one is to reconstruct an amplitude‐preserving PP image with a separated scalar P‐wave particle velocity, which has a clear physical meaning. Numerical examples using two‐dimensional and three‐dimensional models demonstrate that the proposed elastic reverse time migration approach can provide the images with better amplitude‐preserving performance and fewer crosstalk artefacts, compared with the conventional elastic reverse time migration approach based on the scalar product imaging condition.